Development idea of smart forklift / Nur Athirah binti Mohamad Sakri and Muhammad Naim bin Mahyuddin - Mohamad Sakri, Nur Athirah; Mahyuddin, Muhammad Naim (2019)
This study will be focusing on the manufacturing stages, specifically the material handling system of an Industrialised Building System (IBS) component. To run an IBS plant or warehouse, it requires a high number of workers especially skilled worker to handle the movement of the product inside the plant. Other than that, the technologies and machineries used must be safe to ensure the safety and health of the workers. To properly handle an IBS plant, it requires higher technology with accuracy which one of the ways is by replacing the manpower with machineries or robots, since robots works better than human. The main objective of this study is to propose an innovation to cater the problems of material handling of an IBS component in a warehouse or plant. Desk study on relevant research related to the material handling stages and innovation existed will be conducted through a literature review. The data will then be analyses through comparative analysis to come out with the best solution to cater the problems. This study highlights the benefits of having robots in the industry to help human works better and safer as well as following the Industry Revolution 4.0 plan where it is being driven by the conjunction of advanced technologies, such as robotics and artificial intelligence.